Systems approach to problems of the design of automated test complexes. Report 2. Determination of system parameters - Grishko, V.G. (Проблемы прочности, 1985)
In our study, the detection of an extremum for estimates of a set of ATC criteria in a preferred scalar with certain constraints will be understood as optimization.